Graphitic Carbon Nitride for Photocatalytic Hydrogen Production from Water Splitting: Nano-Morphological Control and Electronic Band Tailoring - Yongbo Fan; Xinye Chang; Weijia Wang; Huiqing Fan (Nanomaterials)
Semiconductor polymeric graphitic carbon nitride (g-C3N4) photocatalysts have garnered significant and rapidly increasing interest in the realm of visible light-driven hydrogen evolution reactions. This interest stems from their straightforward synthesis, ease of functionalization, appealing electronic band structure, high physicochemical and thermal stability, and robust photocatalytic activity. This review starts with the basic principle of photocatalysis and the development history, synthetic strategy, and structural properties of g-C3N4 materials, followed by the rational design and engineering of g-C3N4 from the perspectives of nano-morphological control and electronic band tailoring. Some representative results, including experimental and theoretical calculations, are listed to show the advantages of optimizing the above two characteristics for performance improvement in photocatalytic hydrogen evolution from water splitting. The existing opportunities and challenges of g-C3N4 photocatalysts are outlined to illuminate the developmental trajectory of this field. This paper provides guidance for the preparation of g-C3N4 and to better understand the current state of the art for future research directions.